Streifzüge durch eine "fremde" Welt : untersuchung ausgewählter schriftlicher Zeugnisse deutscher Reisender im südlichen Afrika im 19. Jahrhundert unter besonderer Berücksichtigung der kulturellen Fremderfahrung : eine literaturwissenschaftliche Untersuchung - Hemme, Tanja (German Language and Literature, 2017)
In this thesis the written sources of the following travellers have been analysed: Gustav Theodor Fritsch (Drei Jahre in Südafrika, 1868), Theodor Hermann Wangemann (Ein Reise-Jahr in Südafrika, 1868) and Ernst von Weber (Vier Jahre in Afrika, 1878). The main focus is on the perception of the foreign country with its foreign people and different landscape. Each German traveller is studied as a unique example of experiencing the "other" land in his own special way. Travel writings are perceived as scientific, completely rational texts but they contain subjective fictional descriptions of reality as well; the reason why I focussed on the question how a person in the previous century from another continent with a different ideology and mentality reflected the region of Southern Africa. Travelling is at its height in the 19th century, through various continents by different kinds of people. Most of these travellers wanted to gain knowledge about the area visited and its inhabitants in order to "transport" via written texts the facts found and data collected to their European home countries. In my examination these texts are seen as "cultural documents" which express not only the reaction caused by the confrontation with totally foreign forms of life but at the same time they are considered as the indirect representation of the German home culture. The moral values and cultural characteristics of Germany played a significant role during the production of each travelogue. That is the reason why the textual product is also a self-portrayal of the author: his prejudices, his view of the world and his valuation of his home country. The collision of the European and with the so-called Other and the effects on the traveller are of main interest in this thesis. The postmodern theory of the "colonial discourse" was used as an analysing method in order to demonstrate that each encouter with the Other produces a different kind of response from the traveller in its own special environment.